130116 初版
トップページ
有名な変形
\(a_{n+2}-pa_{n+1}+qa_n=0\)
⇔ \(a_{n+2}-\alpha a_{n+1}=\beta(a_{n+1}-\alpha a_n)\)
⇔ \(a_{n+2}-\beta a_{n+1}=\alpha(a_{n+1}-\beta a_n)\)
\(x^2-px+q=0\) を満たす x を,α, β とすると,
解と係数の関係より, p = α + β,   q = αβ
よって, \(a_{n+2}-pa_{n+1}+qa_n=0\) ⇔ \(a_{n+2}-(\alpha+\beta)a_{n+1}+\alpha\beta\cdot a_n=0\)
⇔ \(a_{n+2}-\alpha a_{n+1}=\beta(a_{n+1}-\alpha a_n)\)
⇔ \(a_{n+2}-\beta a_{n+1}=\alpha(a_{n+1}-\beta a_n)\)
例: \(x^2-3x+2=0\) の解は x = 1, 2
\(a_{n+1}-3a_n+2a_n=0\) ⇔ \(a_{n+2}-a_{n+1}=2(a_{n+1}-a_n)\)… (F1)  ⇔ \(a_{n+2}-2a_{n+1}=a_{n+1}-2a_n\)… (F2)